Evaluation of long‐term functional donor‐site morbidity after deep circumflex iliac crest artery bone flap harvest. Issue 4 (29th August 2018) - Rendenbach, Carsten; Goehler, Friedemann; Hansen, Lara; Kohlmeier, Carsten; Amling, Michael; Hanken, Henning; Beck‐Broichsitter, Benedicta; Heiland, Max; Riecke, Bjoern
Abstract: Purpose: Free flap surgery can be associated with donor‐site morbidity. The purpose of this study was to analyze long‐term functional outcomes at the donor site after deep circumflex iliac artery (DCIA) bone flap harvesting. Methods: Fourteen patients (8 men and 6 women, mean age 53.9 years; range 22–87 years) with mandible resection (8 carcinomas, 4 ameloblastomas, 1 osteonecrosis, and 1 myxofibroma) and DCIA flap reconstruction were included in an observational study. Ranges of motion in the hip and lumbar spine, Harris hip score (HHS), jumping mechanography, chair rising, and balance testing were performed on a ground force reaction plate (Leonardo Mechanograph, Novotec Medical GmbH, Germany). The primary outcome was the Esslinger fitness index (EFI, maximum peak power in W/kg normalized to age and gender). Results: Functional assessment was performed preoperatively and 29.0 months postoperatively (range 12–51 months). Mean DCIA flap length was 6.3 cm (range 3.3–10.1 cm). Jaw reconstruction was successful in all cases. HHS (99.2 vs. 97.7 points, P = .004) and all ranges of motion in the lumbar spine and hip joint except for dorsal extension were significantly reduced postoperatively (range −4° to −11.0°). There was no significant difference between pre‐ and postoperative EFI (77.9% vs. 74.28%, P = .591) and body sway (1.25 cm 2 vs. 2.01 cm 2, P = .806). Sensory deficits ( n = 5), load dependent pain ( n = 3), and limitations of daily activities ( n = 3) were subjective complaints. Conclusion: Functional donor site morbidity after DCIA harvesting can be expected to be low in the long‐term.